IMPLEMENTASI METODE TAHSIN DALAM MEMBACA AL-QUR'AN PADA SISWA DI MADRASAH IBTIDAIYAH NEGERI 6 SUKOHARJO - Rofiah Nur Hidayah; Iffah Mukhlisah; Yetty Faridatul Ulfah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to determine the implementation of the tahsin method in reading the Qur'an to students. This type of research is descriptive qualitative research. The subjects in this study were students of grade 5A Madrasah Ibtidayyah Negeri 6 Sukoharjo. Data collection techniques used in this study were interviews, observation and documentation. Meanwhile, data analysis uses data reduction, data presentation and data verification. The results of this study indicate that students are able to follow and can also improve their ability to read the Qur'an through the tahsin method in learning tahfidz. Factors supporting the use of the tahsin method are: the intention and readiness in students, the ability of qualified teachers, the creativity of teachers in the use of methods and the existence of targets in learning. While the inhibiting factors are: lack of teacher control in learning, the feeling of laziness in students, lack of awareness and support of parents in learning tahsin. Nevertheless, the use of the tahsin method shows a success rate of 80% of students' fluency in reading the Qur'an.